Increasing atmospheric antimony contamination in the northern hemisphere: snow and ice evidence from Devon Island, Arctic Canada - Krachler, Michael; Zheng, Jiancheng; Koerner, Roy M.; Zdanowicz, Christian; Fisher, David; Shotyk, William (Journal of environmental monitoring, 2005)
Adopting recently developed clean laboratory techniques, antimony (Sb) and scandium (Sc) deposition were measured in a 63.72 m-long ice core (1842-1996) and a 5 m deep snow pit (1994-2004) collected on Devon Island, Canadian High Arctic. Antimony concentrations ranged from 0.07 to 108 pg g−1 with a median of 0.98 pg g−1 (N = 510). Scandium, used as a conservative reference element, revealed that dust inputs were effectively constant during the last 160 years. The atmospheric Sb signal preserved in the ice core reflects contamination from industrialisation, the economic boom which followed WWII, as well as the comparatively recent introduction of flue gas filter technologies and emission reduction efforts. Natural contributions to the total Sb inventory are negligible, meaning that anthropogenic emissions have dominated atmospheric Sb deposition throughout the entire period. The seasonal resolution of the snow pit showed that aerosols deposited during the Arctic winter, when air masses are derived mainly from Eurasia, show the greatest Sb concentrations. Deposition during summer, when air masses come mainly from North America, is still enriched in Sb, but less so. Snow and ice provide unambiguous evidence that enrichments of Sb in Arctic air have increased 50% during the past three decades, with two-thirds being deposited during winter. Most Sb is produced in Asia, primarily from Sb sulfides such as stibnite (Sb2S3), but also as a by-product of lead and copper smelting. In addition there is a growing worldwide use of Sb in automobile brake pads, plastics and flame retardants. In contrast to Pb which has gone into decline during the same interval because of the gradual elimination of gasoline lead additives, the enrichments of Sb have been increasing and today clearly exceed those of Pb. Given that the toxicity of Sb is comparable to that of Pb, Sb has now replaced Pb in the rank of potentially toxic trace metals in the Arctic atmosphere.